Retractor Plication versus Retractor Plication and Lateral Tarsal Strip for Eyelid Entropion Correction. Issue 2 (March 2014) - Ranno, Stefano; Sacchi, Matteo; Gilardi, Daniela; Lembo, Andrea; Nucci, Paolo
Purpose: Involutional entropion is a common lower lid malposition. Addressing both the horizontal and the vertical lower eyelid laxity in patients with involutional entropion seems to have a more long-lasting effect on maintaining lower eyelid stability; however, there is some disagreement as to which approach is the best surgical intervention. The aim of this study was to determine differences in the surgical outcome of Jones retractor plication (JRP) alone versus Jones retractor plication with a lateral tarsal strip (JRP + LTS) for the treatment of involutional entropion. Methods: A retrospective case series comparison of 118 patients with primary involutional lower eyelid entropion was performed. Jones retractor plication alone was performed in 61 patients, and JRP + LTS in 57 patients. The baseline characteristics of the 2 groups were similar. Patients were retrospectively evaluated from a retrospective case-note review 3 weeks and 6, 12, 18, and 24 months postoperatively. Successful surgery was defined as a normal eyelid position. Results: A total of 115 patients fulfilled the inclusion criteria, 60 in the JRP group and 55 in the JRP + LTS group. Ten patients (16.5%) in the JRP group and 2 patients (3.5%) in the JRP + LTS group had a recurrence of the entropion at or before their 24-month follow-up visit (p = 0.03). Conclusions: These data provide strong evidence that the success rate at 24 months is higher in patients treated with the JRP + LTS procedure compared with JRP alone.